A scalar damage measure for seismic reliability analysis of RC frames. - Jalayer, F.
A scalar damage measure (DM) for probabilistic performance assessment of structures can be expressed as the critical demand-to-capacity ratio corresponding to the component or mechanism that leads the structure closest to failure at the onset of which, the DM assumes the value of one. This DM can be employed to make probabilistic performance assessments taking into account the uncertainty in the ground motion, in the structural modelling parameters, and also in the model(s) used for determining components capacity. Nonlinear dynamic analysis methods can be used to estimate this DM in two ways: (a) applying a (small-size) set of un-scaled ground motion records to the structure and (b) using incremental dynamic analysis. Case (a) is suitable for making performance assessments based on demand and capacity factor design format and case (b) is suitable for estimating directly the probability of failure using numerical integration. Performance assessments using this DM are described in a case study of a RC frame in which the critical demand-to-capacity ratio is determined by taking into account various modes of failure for the limit state of collapse, such as weak storey mechanisms, shear failure in the columns, and ultimate deformations in the columns.
Keywords: Probabilistic performance-based design; Seismic assessment; Reinforced concrete structures; Collapse